Effectiveness Of Tax Return Reporting Via The e-Filling Application - Marfiana, Andri; Kusumawati, Rahayu (Educoretax, 2024)
This study aims to determine the impact of e-Filling on the effectiveness of Tax Return reporting using the D&M IS Success Model. The research subjects are the academic community in the PKN STAN environment who work independently in the Jakarta area and its surroundings. This group was chosen because they are considered to understand the use of e-Filling reporting applications as academics, but some of them still experience difficulties when filling it out. This research uses primary data consisting of 58 responses that have been collected. Data analysis uses the Partial Least Square (PLS) model with Structural Equation Modelling (SEM) methods. The test results indicate that Information Quality, System Quality, and Intention to Use have a significant positive effect on the Net Benefit of the e-Filling System. Additionally, Intention to Use successfully mediates the impact of Information Quality and System Quality on the Net Benefit significantly. The implication for the government is to continue updating the e-Filling system by considering the factors of information quality and system quality and striving to socialize the use of e-Filling to the public.